2016
DOI: 10.12738/estp.2016.5.0126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Social Engagement of Children Having Disabilities with Their Mothers and Fathers

Abstract: Citation: Karaaslan, O. (2016) AbstractThis study examined differences between mothers' and fathers' style of interaction and engagement with their preschool-aged children with Down syndrome (DS) and autism. Data was collected from a sample of 27 mother-child and 27 father-child dyads in which all the children were diagnosed with DS or autism.Participants were both parents and their children from the same family, which allowed comparisons between the mother and father of the same child. Both parents with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In a qualitative study by Oguz and Sönmez (2018) in our country, it was found that mothers of children with ASD exhibit a more sensitive-responsive interaction than the fathers. In another similar study conducted with families with ASD children, it was shown that mothers have more sensitive and more responsive interactions with their children compared to fathers (Karaaslan, 2016). In another (Lovas, 2005) study with typically developing infants, fathers' levels of emotional availability were lower than that of mothers.…”
Section: Discussionmentioning
confidence: 94%
“…In a qualitative study by Oguz and Sönmez (2018) in our country, it was found that mothers of children with ASD exhibit a more sensitive-responsive interaction than the fathers. In another similar study conducted with families with ASD children, it was shown that mothers have more sensitive and more responsive interactions with their children compared to fathers (Karaaslan, 2016). In another (Lovas, 2005) study with typically developing infants, fathers' levels of emotional availability were lower than that of mothers.…”
Section: Discussionmentioning
confidence: 94%